2020
DOI: 10.1136/bmj.m2035
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 care before, during, and beyond the hospital

Abstract: It’s time to shift the research focus to studies on living with this disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…27 28 If the COVID-19 pandemic continues for the next years the PHC has gained important knowledge and experience on how to manage and optimise the care of their patients during such a serious outbreak. 29 However, due to the methodological design of this study we were not able to explore the possible long-term effects of changing the strategy in PHC which is definitely something future researches must investigate.…”
Section: Discussionmentioning
confidence: 92%
“…27 28 If the COVID-19 pandemic continues for the next years the PHC has gained important knowledge and experience on how to manage and optimise the care of their patients during such a serious outbreak. 29 However, due to the methodological design of this study we were not able to explore the possible long-term effects of changing the strategy in PHC which is definitely something future researches must investigate.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, most COVID-19 epidemiological and clinical studies have been hospital-based, 79 and therefore tend to include more severe cases whose findings may not be generalizable to the general population. 10 The objectives of this study were to describe the epidemiological indicators of the early phase of the programme rollout; and to describe the clinical, virologic and natural history features (including hospitalization and deaths) of SARS-CoV-2 infection among patients identified in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, it is not yet clear which risk factors should be considered when managing COVID-19 from the healthcare and public health perspective. 5 Therefore, it is important to distinguish the risk factors for infection by SARS-CoV-2 from those for hospitalisation or death due to COVID-19. A UK study using primary care data found that the risk factors for SARS-CoV-2 infection were increasing age, male gender, population density, socioeconomic deprivation, and black ethnicity.…”
Section: Introductionmentioning
confidence: 99%